Vloga Odbora Združenih narodov proti mučenju pri inkriminaciji mučenja - Pavčič, Urša (Teorija in praksa, 2019)
The article's purpose is to define the role of the United Nations Committee against Torture in criminalising torture in the Republic of Slovenia, as stipulated in Article 1 of the Convention against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment. The analysis reveals the Republic of Slovenia complies considerably with the Committee's recommendations, although this is not evident from the Committee's recommendations at first glance since implementation of the relevant Convention provisions in Slovenia has been characterised by the gradual introduction of measures required to meet the Committee's recommendations and by strengthening and developing of new, increasingly tougher standards for the prohibition of torture and related treatment by the Committee. This latter characteristic negatively affects the Republic of Slovenia's compliance with the Committee's recommendations in the sense that Slovenia's conduct is judged in the light of ever more stringent requirements yet conversely such strict requirements add to the growing level of human rights protection in the country.
Keywords: človekove pravice; mednarodno pravo; Odbor Združenih narodov proti mučenju; OZN; pogodbena telesa OZN; prepoved mučenja; Slovenija; varstvo človekovih pravic